دور الحملات الإعلامية عبر التلفزيون بين سبور لتغطية كأس العلام قطر 2022 وإنعكاساتها على الجمهور الجزائري - *- مريم عبد الحاكم; -*بن فنيش وداد; د/محمد تربح (جامعة عمار ثليجي الاغواط, 2023)
ملخص الدارسة : جاءت دارستنا بعنوان دور الحملات الاعلامية عبر التلفزيون بين سبور لتغطية كأس العالم قطر 2222 ي ائر بقطر وانعكاساتها على الجمهور الجز- دارسة على عينة من طلبة قسم الاعلام وانطلقت دارستنا من إشكالية ،الاتصال بجامعة الأغواط ما دور الحملات الاعلامية في التلفزيون ؟ 2222 لتغطية كأس العالم Bein sport قناة ي ائر بقطر وانعكاساتها على الجمهور الجز ومنه تتفرع الاسئلة الفرعية التالية: بقطر؟2122 لكاس العلم Bein Sport . كيف روجت قنوات 1 في تغطيتها لكاس Bein sport . ما اسلوب عرض رسائل الحملات الإعلامية عبر قنوات 2 ؟ 2122العالم قطر على جمهورها؟2122 في تغطيتها لكأس العالم قطر Bein sport . كيف اثرت حملات 3 و نهدف من خلال دارستنا الى ة Bein التعرف على دور الحملات الاعلامية في التلفزيون قنا بقطر و 2122لتغطية كأس العالم Sport ائري انعكاساتها على الجمهور الجز وكيف ر وجت القناة و التعرف على اسلوب عرضها لرسائل الحملات الإعلامية و التعرف 2122لفعاليات كاس العالم قطر اثر حملاتها على جمهورها. حيث استعملنا المنهج الوصفي كمنهج لدارستنا كما استخدمنا اداة جمع البيانات الاستبيان لجمع بينات طالب بقسم علوم الاعلام والاتصال بجامعة الاغواط والتي اوصلتنا الى 51دارستنا المكونة من النتائج التالية: 2122 لتغطية كأس العالم قطر Bein sport . الحملات الاعلامية التي قامت بها قنوات 1 ائري لمشاهدة استقطبت الجمهور الجز الحدث ة العالمي وجلعت معظمهم يشتركون في باق Bein sport ة وانتظار كاس العالم كما جعت فئة اخرى تبحث عن حلول المشفر غير .2122الاشتارك في الباقة من اجل مشاهدة كأس العالم قطر كانت ناجحة ونسبة كبيرة من الطلبة 2122 لكاس العالم قطر Bein sport . تغطية قنوات 2 يستحق تلك التغطية الاعلامية التي حظي بها من قبل 2122 يرون ان كأس العالم قطر Bein sport قنوات جعلت 2122 في تغطيتها لكأس العالم قطر Bein sport . الحملات الاعلامية لقناة 3 ائري يطلع الجمهور الجز على مختلف اخبار المنتخبات الوطنية معرفة مواعيد وأماكن إقامة و متابعة المباريات وتحليلها 2122المباريات و الإحاطة بكل ما هو جديد عن كأس العالم وانعكست على الجمهور في جعله يهتم بكأس العالم ويتابعه. – الكلمات المفتاحية: الحملات الاعلامية كأس العالم– قنوات بين سبور – التلفزيون Study summary: Our study was titled The Role of Media Campaigns on Television between Sport to Cover the Qatar World Cup 2022 in Qatar and its Repercussions on the Algerian Public - A Study on a Sample of Students of the Department of Media and Communication at the University of Laghouat. Algerian public? From it the following sub-questions branch out: 1. How did Bein sport channels promote the 2022 Flag Cup in Qatar? 2. What is the method of presenting the messages of the media campaigns through the channels of Bein sport in its coverage of the World Cup Qatar 2022? 3. How did Bein Sport's coverage of the 2022 Qatar World Cup affect its audience? Through our study, we aim to identify the role of the media campaigns on television, the Bein sport channel, to cover the 2022 World Cup in Qatar, and its repercussions on the Algerian public, and how the channel promoted the activities of the 2022 Qatar World Cup, and to identify the method of presenting the messages of the media campaigns, and to identify the impact of its campaigns on its audience. Where we used the descriptive approach as a method for our study, and we also used the data collection tool, the questionnaire, to collect the data of our study, which consisted of 50 students in the Department of Information and Communication Sciences at the University of Laghouat, which led us to the following results: 1. The media campaigns carried out by Bein sport channels to cover the Qatar World Cup 2022 attracted the Algerian audience to watch the global event and made most of them subscribe to the encrypted Bein sport package and wait for the World Cup. 2. The coverage of the 2022 Qatar World Cup by Bein sport channels was successful, and a large percentage of students believe that the 2022 Qatar World Cup deserves the media coverage it received from the Bein sport channels. 3. The media campaigns of the Bein sport channel in its coverage of the Qatar World Cup 2022 made the Algerian audience familiar with the various news of the national teams, knowing the dates and places of the matches, and briefing on all that is new about the 2022 World Cup and following the matches and analyzing them, and they reflected on the audience in making them care about the World Cup and follow it. media campaigns - TV - Ben Sport channels - World Cup
دراسة على عينة من طلبة قسم الاعلام الاتصال بجامعة الأغواط